Developing Human Resource Quality Using Traditional Indonesian Puppet Characteristics - Parwita Setya Wardhani; Miya Dewi Suprihandari (Yayasan Rumah Peneleh, 2020)
Puppet is one of the local wealth of Indonesian that we must preserve in addition to many other types of cultural wealth. Historically, puppet also played important role to spread Islam as a new religion. The characters possessed by hundreds of figures of puppets (or wayang) have become one of the educational media for the people of Indonesia since ancient times. This positive characters are passed on to many generations, especially the young. There have been many efforts made to share the virtues of the moral values of wayang, including open discussion and puppet watching activities with several competent speakers who have special expertise regarding the character development activities of the young generation of Indonesia facing the current modern era. It is hoped that from this activity the young generation will develop characters inspired from the characters of wayang so thet they will be capable of competing in the global era. No matter how complex the development of the times, it is hoped that Indonesia's young generation will remain a cultured and powerful generation, as strong as puppet characters who have strong principles in facing global changes.